Dietary intake, nutritional status and mental wellbeing of homeless adults in Reading, UK. Issue 9 (29th November 2017) - Fallaize, Rosalind; Seale, Josephine V.; Mortin, Charlotte; Armstrong, Lisha; Lovegrove, Julie A.
Abstract: Malnutrition has been reported in the homeless, yet the specific nutritional issues faced by each homeless community are unclear. This is in part due to nutrient intake often being compared with dietary reference values as opposed to a comparative housed population. In addition, the complex interplay between nutrient intake, reward mediated behaviour and mental illness is frequently overlooked. This study aimed to compare the dietary intake, nutritional status and mental wellbeing of homeless and housed adults. Homeless ( n 75) and matched housed ( n 75) adults were recruited from Reading (UK). Nutrient intake was determined using the European Prospective Investigation into Cancer and Nutrition Norfolk FFQ. The Patient Health Questionnaire: Somatic Anxiety Depressive Symptoms (PHQ-SADS) assessed for signs of mental illness. Demographic, behavioural and physiological information was collected using closed-ended questions and anthropometric measurements. Overall, dietary intake was poorer in homeless adults who reported higher intakes of salt (8·0 v . 6·4 g, P =0·017), SFA (14·6 v . 13·0 %, P= 0·002) and alcohol (5·3 v . 1·9 %, P <0·001) and lower intakes of fibre (13·4 v . 16·3 g, P <0·001), vitamin C (79 v . 109 mg, P <0·001) and fruit (96 v . 260 g, P <0·001) than housed. Smoking, substance misuse and PHQ-SADS scores were also higher in the homeless ( P <0·001). Within the homeless population, street homeless ( n 24) had lower SFA (13·7 v .15·0 %, P= 0·010), Ca (858 v . 1032 mg, P =0·027) and milk intakes (295 v . 449 g, P= 0·001) than hostel residents ( n 51), which may reflect the issues with food storage. This study highlights the disparity between nutritional status in homeless and housed populations and the need for dietary intervention in the homeless community.